WILDFIRE DYNAMICS AND ITS EFFECTS ON THE FOREST RESOURCES AND PUBLIC PROPERTY IN NEPAL - Bhujel, Krishna Bahadur; Byanju, Rejina Maskey; Gautam, Ambika P. (Journal of Institute of Science and Technology, 2019)
NASA (National Aeronautics and Space Administration) has detected several intensive wildfires from the local to global level in 2016. However, deeper study on the dynamics of wildfire and its consequences are still inadequate. This study was carried out to find wildfire dynamics and its effects on the forest resources and public property in Nepal. Moderate Resolution Imaging Spector-Radiometer (MODIS) was used for active fire data of 2016 in Nepal. Wildfire-related national and international published articles, report, website and media were reviewed. Data were analyzed using ArcGIS and MS Excel. The result showed an abnormal wildfire incidence areas in 2016, adverse effect on the forest resources and public property. One hundred forty burnt days were recorded. Density of wildfire incidence and burnt area were found to be 0.09 number and 3.4 hectares per km2, respectively, which was around 33 % more than of the last 15 years. The huge forest resources and its tangible as well as intangible services were lost during the year of 2016. Loss of forest resources account for about NRs 11,750,000 (US 107,798) as per local market price for the year. Total eleven people were killed and over hundred people injured. The findings of the present study will be useful baseline information for implementers, researchers and decision-makers in future.